Predictive strength of Macroeconomic Imbalance Procedure indicators - Biegun, Krzysztof; Dahl, Martin; Karwowski, Jacek (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The Macroeconomic Imbalance Procedure (MIP) is a key step in the European Semester, aimed at the coordination of the economic policies of the EU Member States to prevent excessive macroeconomic imbalances in the EU and support structural reforms. The MIP was originally envisaged as a legal tool for crisis prevention, allowing macroeconomic imbalances to be detected and then remedied, but is also used as an Early Warning System. However, the real strength of MIP indicators to predict crises has not been proved in practice and is widely contested in the literature. Aim: Fourteen scoreboard (“main”) and 28 auxiliary MIP indicators are currently in use. This paper is aimed at the assessment of the power of all MIP indicators in predicting crises. Results: The added value of our research is to test the MIP’s ability to predict changes in GDP, which may be considered as a proxy for the deterioration or improvement of the economic situation. Very little investigation has been done in this area so far. In addition, to our knowledge, no research papers have investigated the relevance of auxiliary MIP indicators. Our results show that only four main indicators (house price index, nominal unit labour cost index, general government sector debt, and export market shares) and another four auxiliary indicators (residential construction as percentage of GDP, activity rate, people living in households with very low work intensity, and export performance against advanced economies) seem to be able to predict the upcoming crises.